Pengaruh Bauran Promosi dan Physical Evidence terhadap Keputusan Pengunjung pada Candi Muara Jambi - Fiza Fradesa (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study raised concerns about the influence of the promotion mix and physical evidence that will have an impact on visitor decisions. This research was conducted in the exact scope of the Muara Jambi Temple. The visitor's decision is one of the main problems that are always faced by various tourist attractions. Therefore, it is important for tourist attractions to increase promotion and physical evidence to provide what visitors want. The purpose of this study was to determine the effect of the promotion mix, physical evidence, and visitor decisions on the Muara Jambi Temple, to determine the effect of the promotional mix and physical evidence on simultaneous visitor decisions on the Muara Jambi Temple, and to determine the effect of the promotional mix and physical evidence on visitor's decision partially at the Muara Jambi Temple. To check the problem above the survey was conducted by distributing questionnaires to the visitors of the temple. The results of the questionnaire were analyzed descriptively and verifiatively. The analytical tool in this study uses multiple linear regression with proof of hypothesis by F statistical tests and t statistical tests. The results of this study indicate that the statistical test F variable promotional mix (X1) has an influence on visitor decisions, while the physical evidence variable (X2) has no influence on visitor decisions